2019
DOI: 10.1021/acs.biochem.9b00155
|View full text |Cite
|
Sign up to set email alerts
|

An Active, Ligand-Responsive Pulling Geometry Reports on Internal Signaling between Subdomains of the DnaK Nucleotide-Binding Domain in Single-Molecule Mechanical Experiments

Abstract: Single-molecule mechanical experiments have proven to be ideal tools for probing the energetics and mechanics of large proteins and domains. In this paper, we investigate the nucleotide-dependent unfolding mechanics of the nucleotide-binding domain (NBD) of the Hsp70 chaperone DnaK. The NBD binds ADP or ATP in the binding cleft formed by lobe I and lobe II, which consists of two subdomains each. When force is applied to the termini of the NBD, the observed unfolding forces are independent of the nucleotide sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…For the last two decades, [1] smFRET techniques have been extensively used to study the properties of molecular machines, [2] intrinsically disordered proteins (IDPs),[ 3 , 4 , 5 , 6 , 7 , 8 ] protein folding processes,[ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] protein‐ligand[ 17 , 18 , 19 ] and protein‐nucleic acid interactions,[ 20 , 21 , 22 , 23 ] as well as other structure‐function relationships and dynamic processes. [ 24 , 25 , 26 ] SmFRET is a particularly powerful and versatile tool to gain molecular and mechanistic insights because of its high spatial resolution (2–10 nm) combined with a wide range of accessible timescales (ns‐minutes). [ 1 , 10 , 27 ] In fact, smFRET is becoming increasingly popular in the investigation of membrane transporter dynamics (Table 1 ), thus complementing well‐established methods such as Nuclear Magnetic Resonance (NMR),[ 28 , 29 , 30 ] Small‐Angle X‐ray Scattering (SAXS)[ 31 , 32 , 33 ] and Electron Paramagnetic Resonance (EPR).…”
Section: Introductionmentioning
confidence: 99%
“…For the last two decades, [1] smFRET techniques have been extensively used to study the properties of molecular machines, [2] intrinsically disordered proteins (IDPs),[ 3 , 4 , 5 , 6 , 7 , 8 ] protein folding processes,[ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ] protein‐ligand[ 17 , 18 , 19 ] and protein‐nucleic acid interactions,[ 20 , 21 , 22 , 23 ] as well as other structure‐function relationships and dynamic processes. [ 24 , 25 , 26 ] SmFRET is a particularly powerful and versatile tool to gain molecular and mechanistic insights because of its high spatial resolution (2–10 nm) combined with a wide range of accessible timescales (ns‐minutes). [ 1 , 10 , 27 ] In fact, smFRET is becoming increasingly popular in the investigation of membrane transporter dynamics (Table 1 ), thus complementing well‐established methods such as Nuclear Magnetic Resonance (NMR),[ 28 , 29 , 30 ] Small‐Angle X‐ray Scattering (SAXS)[ 31 , 32 , 33 ] and Electron Paramagnetic Resonance (EPR).…”
Section: Introductionmentioning
confidence: 99%
“…Hsp70 consists of 638 amino acid residues that belong to either mechanically stable or unstable protein substructures (Figure 1a)-based on our previous research [16,17,19,20]. For our analysis, we excluded residues 604-638 because they belong to a low-complexity intrinsically disorder sequence, which differs dramatically from the folded substructures.…”
Section: Analysis Of the Stable And Unstable Substructures Of Hsp70mentioning
confidence: 99%
“…Hence, some of the challenges are inherent to the cooperative nature of substructures and to the mechanical anisotropy of proteins, which means that the mechanical properties of proteins are highly dependent on pulling orientation [13][14][15][16]. Single-molecule studies showed that during the unfolding of large proteins, folded protein substructures are disrupted in distinct and well-defined steps [16][17][18][19][20][21][22][23][24][25]. The high reproducibility and specificity of these microscopic unfolding steps indicates a significant level of cooperativity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is one of the most conserved proteins, with 40-60% identity between prokaryotic and eukaryotic homologues [43], and it plays key roles in protein folding, disaggregation, and degradation [44,45]. The E. coli homologue of the Hsp70 chaperone, DnaK, is probably the most thoroughly studied [46], and it has been extensively studied using optical trap experiments in our laboratory for a number of years [47][48][49][50]. Hsp70 can be divided into two major subunits, the nucleotide-binding domain (NBD) and the substrate-binding domain (SBD), both of which undergo conformational changes as a result of binding either the nucleotide or a substrate peptide.…”
Section: Hsp70mentioning
confidence: 99%